Identification of Volatile Oil Components of Croton oblongus - Wan Mohd Nuzul Hakimi Bin Wan Salleh (Tanjung Malim, 2024)
Identification of Volatile Oil Components of Croton oblongus by Wan Mohd Nuzul Hakimi Bin Wan Salleh